2015
DOI: 10.3174/ajnr.a4534
|View full text |Cite
|
Sign up to set email alerts
|

Texture Feature Ratios from Relative CBV Maps of Perfusion MRI Are Associated with Patient Survival in Glioblastoma

Abstract: Background and Purpose Texture analysis has been applied to medical images to assist in tumor tissue classification and characterization. In this study, we obtained textural features from parametric (rCBV) maps of dynamic susceptibility contrast-enhanced magnetic resonance imaging images in glioblastoma and assessed their relationship with patient survival. Materials and Methods MR perfusion data of 24 patients with glioblastoma from the Cancer Genome Atlas was analyzed in this study. One- and two-dimensiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
50
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 23 publications
3
50
0
Order By: Relevance
“…Distinct from the commonly used univariate statistical features, our filters capture the spatial information of a voxel in its local neighborhood in DKI images, where our bar and edge filter could detect the enhanced vascular structure of tumor typing at different scales, and capture its local context cues. Our features also differ from another set of texture features using popular Grey-Level Concurrence Matrix (GLCM) and its associated statistics, which usually considered features at a single scale (e.g., on raw intensities) and sensitive to image resolutions 23 . Our study has also demonstrated the superiority of using texture features for determination of IDH mutation status, given the same number of biomarkers (e.g., we selected 4 biomarkers in our study), the AUC value of using texture biomarkers has improved by 49% (0.88 vs 0.59) compared with that of using first-order statistical biomarkers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Distinct from the commonly used univariate statistical features, our filters capture the spatial information of a voxel in its local neighborhood in DKI images, where our bar and edge filter could detect the enhanced vascular structure of tumor typing at different scales, and capture its local context cues. Our features also differ from another set of texture features using popular Grey-Level Concurrence Matrix (GLCM) and its associated statistics, which usually considered features at a single scale (e.g., on raw intensities) and sensitive to image resolutions 23 . Our study has also demonstrated the superiority of using texture features for determination of IDH mutation status, given the same number of biomarkers (e.g., we selected 4 biomarkers in our study), the AUC value of using texture biomarkers has improved by 49% (0.88 vs 0.59) compared with that of using first-order statistical biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…By doing so, our method could avoid redundancy between selected features (the redundancy refers to the case where the two features essentially carry the same information) but include features which has complementary information for tumor grade or mutation prediction. This can be treated as an advantage compared with the methods that rank features individually 23,25 .…”
Section: Discussionmentioning
confidence: 99%
“…These results, obtained using shape features, are also complementary to previous studies, suggesting a link between phenotype texture and the survival of patients with GBM. 22,[35][36][37] This study is also related to recent work establishing a link between image features, based on spatial habitats 38 and texture (i.e. fractal texture analysis, histogram of oriented gradients, run length, local binary patterns and Haralick features) 39 and the 12-month survival status of patients with GBM.…”
Section: Discussionmentioning
confidence: 99%
“…a Information measure of correlation, compactness, and inverse correlation are texture features that have been previously applied to classify gliomas by degree of malignancy 54 and to predict survival outcomes in grade IV gliomas. 55 Detailed equations for these texture features are described elsewhere. 55,56 NeuroOncology combined model.…”
Section: Discussionmentioning
confidence: 99%
“…55 Detailed equations for these texture features are described elsewhere. 55,56 NeuroOncology combined model. This observation underscores the advantage of using a machine-learning algorithm to discover and integrate synergistic multimodal imaging features.…”
Section: Discussionmentioning
confidence: 99%